2019
DOI: 10.1155/2019/5863476
|View full text |Cite
|
Sign up to set email alerts
|

C4d Deposition in Fetal Vessels of the Placenta in Neonatal Lupus Syndrome

Abstract: Neonatal lupus syndrome (NLS) is a rare, passively acquired autoimmune syndrome caused by maternal autoantibodies. We describe a case of a newborn with NLS and the accompanying placental findings. A female neonate was born by emergency cesarean delivery due to non-reassuring fetal status at 35 weeks and 3 days. This neonate had congenital erythematous and scar lesions on the face, back, and upper and lower extremities. Maternal and fetal anti-SSA and SSB antibodies were elevated and this baby was diagnosed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Detection of deposited C4d complexes is considered nowadays to be the gold standard for the diagnosis of acute humoral resection of kidney transplantation [79]. However, further research is needed to demonstrate the usefulness of C4d deposition as a new NLE marker [80].…”
Section: Characteristics Of Neonatal Lupusmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of deposited C4d complexes is considered nowadays to be the gold standard for the diagnosis of acute humoral resection of kidney transplantation [79]. However, further research is needed to demonstrate the usefulness of C4d deposition as a new NLE marker [80].…”
Section: Characteristics Of Neonatal Lupusmentioning
confidence: 99%
“…It is suggested that C4d could be used as a biomarker used to evaluate the future risk of FGR and to control the disease during pregnancy in the case of these patients [81]. In summary, Sato et al determined the diagnosis of the newborn on the basis of skin symptoms, antibody levels in the serum of the newborn and mother, and histopathological examinations of the placenta [80].…”
Section: Characteristics Of Neonatal Lupusmentioning
confidence: 99%
“…Более того, C4d является общепринятым биомаркером при опосредованном антителами отторжении трансплантата, а также играет роль в опосредованных антителами осложнениях беременности. Интересно, что плацентарный C4d, обнаруживаемый в большинстве случаев системной красной волчанки и антифосфолипидного синдрома, диффузно экспрессируется в синцитиотрофобласте [3].…”
Section: Discussionunclassified